Pengaruh Metode Pengeringan terhadap Kadar Flavonoid Total pada Daun Jinten (Coleus amboinicus Lour) - Elok Widayanti; Jasmine Mar’ah Qonita; Retno Ikayanti; Nurma Sabila (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Cumin leaf are medicinal plants that are used as treatment and useful for health. Cumin leaf contain secondary metabolites, one of which is flavonoids. Flavonoids are the largest phenolic compounds found in plants and function as antioxidant, antibacterial, antiviral, anti-inflammatory, antiallergic, and anticancer activities. The flavonoid content of a plant can be affected by the drying temperature in the manufacture of simplicia. The purpose of this study was to determine the total flavonoid content in cumin leaf if dried by several drying methods. In this study, cumin leaf simplicia was used with different drying methods, namely sun drying, wind drying, and oven drying. The simplicia powder was extracted using ethanol and then tested quantitatively using a UV-Visible Spectrophotometer at a wavelength of 440 nm. Total flavonoid content by sun drying, oven drying, and wind drying was 3,38 mg QE/g extract, 3,58 mg QE/g extract, and 5,83 mg QE/g extract respectively. Based on the research on the flavonoid test on cumin leaves with different drying methods, the lowest average total flavonoid content was obtained on Sun drying was 3.38 mg QE/g extract and the highest was wind drying with 5.83 mg QE/g extract while oven drying was 3.58 mg QE/g extract.